Is it the time to integrate novel sequencing technologies into clinical practice?. Issue 2 (30th March 2023) - VanOudenhove, Jennifer; Halene, Stephanie; Mendez, Lourdes
Abstract : Purpose of review: The aim of this study was to provide insight into how novel next-generation sequencing (NGS) techniques are set to revolutionize clinical practice. Recent findings: Advances in sequencing technologies have focused on improved capture of mutations and reads and cellular resolution. Both short and long read DNA sequencing technology are being refined and combined in novel ways with other multiomic approaches to gain unprecedented biological insight into disease. Single-cell (sc)DNA-seq and integrated scDNA-seq with immunophenotyping provide granular information on disease composition such as clonal hierarchy, co-mutation status, zygosity, clonal diversity and genotype phenotype correlations. These and other techniques can identify rare cell populations providing the opportunity for increased sensitivity in measurable residual disease monitoring and precise characterization of residual clones permitting distinction of leukemic from pre/nonmalignant clones. Summary: Increasing genetics-based mechanistic insights and classification of myeloid diseases along with a decrease in the cost of high-throughput NGS mean novel sequencing technologies are closer to being a reality in standard clinical practice. These technologies are poised to improve diagnostics, our ability to monitor treatment response and minimal residual disease and allow the study of premalignant conditions such as clonal haematopoiesis.